Prediction of future disposal of end-of-life refrigerators containing CFC-11 - ÇALLI, BARIŞ; CAN, ZEHRA SEMRA (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The objective of this study was to predict the number of refrigerators containing CFC-11 blown isolation foam and the amount of CFC-11 banked in these refrigerators. By using a Weibull-based survival function, the number of CFC-11 containing and still-functioning refrigerators was estimated to be approximately 1.6 million in 2013 in Turkey. In order to determine the amount of CFC-11 in the isolation foam of these refrigerators, polyurethane (PU) foam samples were taken from a refrigerator manufactured in 1993 and the quantity of CFC-11 was analyzed by a GC-MS. It was determined that 113-195 mg CFC-11/g PU remains in the PU foam depending on the location such as door, sides, top and bottom. Knowing that a mid-sized refrigerator contains 4 kg PU on average, the total amount of PU foam to be disposed of is 6344 tons when the CFC-11 containing refrigerators in Turkey become obsolete in the near future. Furthermore, 717-1237 tons of CFC-11 are expected to be banked in the PU foam of these refrigerators which will exert an equivalent amount of ozone depleting potential (ODP). In addition, the global warming potential will vary between 3.4 and 5.9 million tons of CO2. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: CFCs; End-of-life refrigerators; Global warming; Ozone depleting potential; Polyurethane foam; POLYURETHANE FOAM WASTE; FLUOROCARBONS; APPLIANCES; RELEASE